1989
DOI: 10.1111/j.1532-5415.1989.tb07279.x
|View full text |Cite
|
Sign up to set email alerts
|

Age‐Related Changes of Thyroid Function and Immunologic Abnormalities in Patients with Hyperthyroidism Due to Graves' Disease

Abstract: In order to clarify the reasons why hyperthyroidism due to Graves' disease is mild in aged patients compared to young patients, we examined the degree of hyperthyroidism and immune abnormalities in 371 untreated patients. The patients were divided into nine groups based on their age; groups A to I consisted of patients aged 0-9, 10-19, 20-29, 30-39, 40-49, 50-59, 60-69, 70-79, and 80-89 years, respectively. Serum thyroxine (T4), triiodo-thyronine (T3), and thyroglobulin levels were highest in group B (patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
15
2

Year Published

1991
1991
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 18 publications
5
15
2
Order By: Relevance
“…As known, the prevalence of Graves' patients is associated to gender, and, in accordance with this view, our subjects were predominant female (85.6% females, 24.4% males). Nevertheless, differently with previous reports [24,25], any correlation between gender and relapse(s) was detected (p = 0.973). In a subgroup of women affected by GD, and after pregnancy, age resulted associated to relapse [26]; again, our data didn't show any correlation between age and this risk; probably it may due to different selection of patients.…”
Section: Discussioncontrasting
confidence: 99%
“…As known, the prevalence of Graves' patients is associated to gender, and, in accordance with this view, our subjects were predominant female (85.6% females, 24.4% males). Nevertheless, differently with previous reports [24,25], any correlation between gender and relapse(s) was detected (p = 0.973). In a subgroup of women affected by GD, and after pregnancy, age resulted associated to relapse [26]; again, our data didn't show any correlation between age and this risk; probably it may due to different selection of patients.…”
Section: Discussioncontrasting
confidence: 99%
“…FreeT 3 -index and freeT 4 -index are lower in the older age groups, as reported previously in several studies (7,9,19). Serum TBII also decreased with advancing age, again in agreement with the literature (7).…”
Section: Discussionsupporting
confidence: 92%
“…Age has consistently been observed as a significant modulating factor, advancing age being associated with less severe Graves' hyperthyroidism (7)(8)(9). The mechanism behind less severe Graves' hyperthyroidism in the older age groups is incompletely understood.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, determinants for levels of serum T 3 and T 4 have not been studied in detail even if previous studies reported on various details such as influence of age (2,3), sex (3), iodine intake (4), and TSH receptor antibody (TRAb) concentration (5,6). Limited patient characteristics were included in most of these studies, and often they did not take various possible confounders into account, such as smoking, known to aggravate iodine deficiency (7) and to modulate thyroid autoimmunity (8), alcohol intake that besides from influencing the risk of Graves' disease (GD) (9) also may supply flavonoids known to modulate the selenodeiodinase activity (10), intake of vitamin supplements often containing iodine, and co-morbidity.…”
Section: Introductionmentioning
confidence: 99%